KINDS OF TRANSLATIONS USED FROM MAHEN'S SONG "PURA PURA LUPA" BY EMMA HEESTERS - Utami Rosalina; Veronika Simbolon (Tomorrow's Education Journal, 2023)
This study aims to identify the types of translation used in translating Mahen's song "Pura Pura Lupa" translated by Emma Heesters. The method used in this research is a descriptive-qualitative method. In analyzing the data, the researcher used various translation theories put forward by Larson. The results of the study show that there are 19 data found in the translation of Mahen's song "Pura Pura Lupa" translated by Emma Heesters. Of the 19 data, there are 3 types of translation used, namely modified literal translation (10 data), idiomatic translation (3 data) and inappropriate free translation (6 data). Modified literal translation is widely used in translating song lyrics because the translator adds information in the target language and changes the meaning from the source language to the target language to create a special reaction for the target language listeners